Resiliensi Sosial Nelayan Udang dalam Menjaga Stabilitas Ekonomi di Tengah Perubahan Iklim di Tambak Mulyo Kota Semarang - Nadia Nadia; Atika Wijaya (Universitas Pendidikan Ganesha, 2025)
Climate change has a significant impact on the marine sector and poses a serious threat to the livelihoods of coastal communities. One area that has felt the real impact of these conditions is Tambak Mulyo, Semarang City, Central Java. The vast sea that surrounds it is rich in shrimp, leading most of the local community to work as shrimp fishermen. However, climate change has hindered their productivity and caused income instability. This study aims to (1) examine the work culture of shrimp fishermen, (2) describe the impacts of climate change on their working patterns, and (3) analyze the forms of social resilience practiced by shrimp fishermen in Tambak Mulyo through Keck and Sakdapolrak’s theory of social resilience, which consists of three main aspects: coping, adaptive, and transformative capacities. This research employs a qualitative method using a case study approach. The data were obtained through participant observation, semi-structured interviews, documentation, and a literature review of articles relevant to the research topic. The results show that shrimp fishermen in Tambak Mulyo experience income decline due to unpredictable weather. However, they endure these challenges through social resilience, including work diversification, family involvement in economic activities, and the nombok (debt pay-later) system. Therefore, this study highlights that cooperation and strong social ties are vital to sustaining community resilience. These findings are particularly important because Tambak Mulyo serves as a major shrimp production center that remains highly vulnerable to the complex impacts of climate change.